2016
DOI: 10.3372/wi.46.46202
|View full text |Cite
|
Sign up to set email alerts
|

Henckelia wijesundarae(Gesneriaceae), a new endemic species from Sri Lanka, and lectotypification ofChirita walkeraeandC. walkeraevar.parviflora

Abstract: A new species, Henckelia wijesundarae, endemic to Hiniduma, Galle, Sri Lanka, is described and illustrated. Diagnostic features of the new species are discussed and compared to the closely allied species H. walkerae. Based on fieldwork studies, we propose an IUCN conservation status of Critically Endangered (CR) for H. wijesundarae. At the same time we lectotypify the names Chirita walkerae (the basionym of H. walkerae) and C. walkerae var. parviflora (treated here in the synonymy of H. wijesundarae).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We believe that the habitat driven speciation is worthy of further investigation. Although a large number of new species of Gesneriaceae have been reported from China in recent years, until now, no new members of Henckelia have been published after the revision (Weber et al 2011) from China, and a few new species of the genus have been described from India, Sri Lanka, Myanmar and Thailand (Manudev et al 2012; Janeesha and Nampy 2015; Ranasinhe et al 2016; Krishna and Lakshminarasimhan 2018; Sirimongkol et al 2019). The two new species in this paper were all discovered in Dawei Mountain area, a locality with several different vegetation types and abundant plant diversity; therefore, we will continue to pay more attention to the Gesneriaceae species diversity in this area and adjacent region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the habitat driven speciation is worthy of further investigation. Although a large number of new species of Gesneriaceae have been reported from China in recent years, until now, no new members of Henckelia have been published after the revision (Weber et al 2011) from China, and a few new species of the genus have been described from India, Sri Lanka, Myanmar and Thailand (Manudev et al 2012; Janeesha and Nampy 2015; Ranasinhe et al 2016; Krishna and Lakshminarasimhan 2018; Sirimongkol et al 2019). The two new species in this paper were all discovered in Dawei Mountain area, a locality with several different vegetation types and abundant plant diversity; therefore, we will continue to pay more attention to the Gesneriaceae species diversity in this area and adjacent region.…”
Section: Discussionmentioning
confidence: 99%
“…Henckelia s.l. consists of more than 60 species, mainly distributed across south and east Asia and the adjacent Himalayan regions (Weber et al 2011; Manudev et al 2012; Janeesha and Nampy 2015; Sinha and Datta 2016; Ranasinhe et al 2016; Krishna and Lakshminarasimhan 2018; Sirimongkol et al 2019). Southwest China harbors a high diversity of Henckelia , and more than 20 species of Henckelia , which were originally described under the names of Hemiboeopsis W.T.…”
Section: Introductionmentioning
confidence: 99%
“…Petrocosmea has more than 50 known species distributed in China, Vietnam, Thailand and India (Han et al 2018b); Didymocarpus has approximately 70 species range from northwest India, eastwards through Nepal, Bhutan, northeast India, Myanmar, to southern China, Vietnam, Laos, Cambodia, Thailand, the Malay Peninsula and northwards to Sumatra (Weber and Burtt 1998; Weber et al 2000; Möller et al 2016a; Hong et al 2018); Henckelia has 64 known species found in Sri Lanka, southern and north-eastern India, Nepal, Bhutan, southern China, northern Laos, northern Vietnam and northern Thailand (Weber et al 2011; Sirimongkol et al 2019). After thorough comparisons of diagnostic morphological, anatomical features and herbarium specimens available at BM, E, HITBC, K, KUN, NYBG and P with similar taxa of Petrocosmea , Didymocarpus , and Henckelia , and consulting the relevant literature for Petrocosmea (Wang 1985; Wang et al 1990, 1998; Burtt 1998a; Li and Wang 2004; Wei and Wen 2009; Gou et al 2010; Middleton and Triboun 2010; Zhao and Shui 2010; Shaw 2011; Xu et al 2011; Qiu and Liu 2015; Qiu et al 2011, 2012, 2015a, 2015b; Wang et al 2013; Zhang et al 2013; Han et al 2017, 2018a, 2018b), Didymocarpus (Wang et al 1998; Burtt 1998b, 1999, 2001; Weber et al 2000; Hilliard 2001; Li and Wang 2004; Nangngam and Maxwell 2013; Wen et al 2013; Li and Li 2014; Nangngam and Middleton 2014; Phuong et al 2014; Li and Wang 2015; Cai et al 2016; Joe et al 2016; Hong et al 2018), and Henckelia (Wang et al 1998; Weber and Burtt 1998; Burtt 2001; Weber et al 2011; Middleton et al 2010; Ranasinghe et al 2016; Sirimongkol et al 2019) from China and adjacent regions, it was confirmed that the four specie...…”
Section: Introductionmentioning
confidence: 99%
“…Burtt. The genus under its current definition is distributed in Sri Lanka, India, Myanmar, Nepal, Bhutan, southern China, northern Vietnam, northern Laos, and northern Thailand. A few species were recently described bringing the total number to c. 70 species worldwide (Manudev et al, 2012;Middleton et al, 2013;Kumar, 2014;Janeesha & Nampy, 2015;Ranasinghe et al, 2016;Krishna & Lakshminarasimhan, 2018;Borah et al, 2019;Cai et al, 2019;Sirimongkol et al, 2019;Yang et al, 2019;Kanthraj et al, this issue). It is the eighth largest genus in tribe Trichosporeae and tenth largest in subfamily Didymocarpoideae (Möller & Clark, 2013).…”
Section: Introductionmentioning
confidence: 99%